Adhesive for aramid fiber reinforced composite pipe as well as preparation method and application of adhesive
Through the method of dopamine surface modification and specific adhesive composition, the bonding problem between aramid fiber and EVOH layer is solved, the bonding strength and pressure bearing capacity of the composite tube are improved, and the needs of a variety of pipe applications are met.
Patent Information
- Application Number
- CN202411399072.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-10-09
AI Technical Summary
Aramid fiber reinforced composite tubes are prone to delamination and separation during use, resulting in poor adhesion and affecting product quality.
The surface modification of aramid fibers was performed using dopamine solution, and the adhesive composed of ethylene-vinyl alcohol copolymer, reactive phenolic resin and inorganic nanoparticles was prepared by mixing and forming an adhesive. The bonding treatment is carried out at specific temperatures and pressures to enhance the bonding effect of the aramid fiber to the EVOH layer.
It realizes a firm bond between the aramid fiber reinforced layer and the EVOH barrier layer, improves the pressure bearing capacity and heat resistance of the composite pipe, and meets the requirements of a variety of pipe application fields.
Smart Images

Figure BDA0005074682000000061
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of aramid fiber reinforced composite pipe production, and specifically relates to an adhesive for aramid fiber reinforced composite pipe and a preparation method and application thereof. Background Art
[0002] Flexible composite pipes are generally multi-layer structures, consisting of an inner layer, a barrier layer, a reinforcement layer, an outer layer, and an adhesive layer between the layers. The reinforcement layer is mostly made of fiber materials. Aramid fiber is an organic polymer fiber first developed by DuPont in the United States. Its full name is "polyphenylene phthalate". It has high strength, good toughness, high modulus, low density, corrosion resistance, and good thermal stability. Its strength is 5 to 6 times that of steel wire, its modulus is 2 to 3 times that of steel wire or glass fiber, its toughness is 2 times that of steel wire, and its weight is only about 1 / 5 of that of steel wire. It does not decompose at a temperature of 560 degrees. Aramid fiber also has good insulation and anti-aging properties and has a long life cycle.
[0003] Glass fiber and carbon fiber are also common reinforcing materials. Although glass fiber is low in cost, its mechanical properties are not as good as aramid fiber. Carbon fiber has high strength and modulus but is too expensive. Aramid fiber combines the advantages of these two fibers and is an ideal reinforcing material. It is very suitable for use as the reinforcing layer of composite pipes. Aramid fiber reinforced composite pipes are mainly used for oil and gas transportation, urban gas network projects, shallow sea oil and gas pipelines, etc.
[0004] Ethylene-vinyl alcohol copolymer (EVOH) is a high-performance barrier material. In addition to excellent processability and extraordinary barrier properties to odors and solvents, it also has the characteristics of transparency, gloss, elasticity, good wear resistance and weather resistance, and high mechanical strength. Moreover, EVOH has the highest thermal stability among barrier resins, and waste can be recycled and reused, making it very suitable for use as a barrier layer for composite pipes.
[0005] Since aramid fiber has a highly crystalline molecular chain structure and the benzene ring in the molecular structure has a large steric hindrance, its surface is smooth and has low surface energy. In addition, the surface of aramid fiber lacks chemically active functional groups and has low reactivity, resulting in poor interfacial adhesion with most substrates. During use, aramid fiber reinforced composite pipes are very prone to delamination and separation, which seriously affects the quality of the product. Summary of the invention
[0006] The purpose of the present invention is to provide an adhesive for aramid fiber reinforced composite pipes and a preparation method and application thereof, so as to overcome the shortcomings of the prior art. One of the purposes of the present invention is to provide an adhesive for aramid fiber reinforced composite pipes, which has good bonding performance and is suitable for bonding aramid fiber layers and EVOH layers. The adhesive has good bonding effects on both aramid fibers and EVOH. The preparation process of the adhesive is simple, the raw materials are easily available, and it is easy for large-scale industrial production.
[0007] The second purpose of the present invention is to provide a method for using an adhesive for aramid fiber reinforced composite pipes, which adopts aramid surface modification technology combined with adhesive technology to achieve strong bonding between the two layers. The modification method is green and environmentally friendly and does not damage the mechanical properties of the aramid fiber itself. The aramid fiber reinforcement layer and the EVOH barrier layer after bonding have firm bonding, high pressure bearing capacity and good heat resistance.
[0008] To achieve the above object, the present invention is implemented through the following technical solutions:
[0009] Technical solution one: An adhesive for aramid fiber reinforced composite pipe, made from the following components in weight ratio: 40-60 parts of ethylene-vinyl alcohol copolymer, 10-25 parts of reactive phenolic resin, 10-25 parts of compatibilizer, 0.5-1 part of inorganic nanoparticles, and 0.5-1 part of antioxidant; the inorganic nanoparticles are any one of silicon dioxide, zinc oxide, and titanium dioxide.
[0010] Technical solution 2: A method for preparing an adhesive for aramid fiber reinforced composite pipes, comprising mixing 40-60 parts of ethylene-vinyl alcohol copolymer, 10-25 parts of reactive phenolic resin, 10-25 parts of compatibilizer, 0.5-1 part of inorganic nanoparticles, and 0.5-1 part of antioxidant, adding the mixture into a twin-screw extruder for mixing at a mixing temperature of 190-210°C and a screw speed of 300-350 rpm, extruding and granulating to obtain a solid adhesive.
[0011] The melt flow rate of the ethylene-vinyl alcohol copolymer is 2.0-6.0 g / 10 min, the melting temperature is above 190° C., and the molecular weight is 180,000-200,000; the reactive phenolic resin is an isocyanate-modified phenolic resin with a molecular weight of 1.22-1.25 million.
[0012] The compatibilizer is any one of ethylene-vinyl acetate copolymer, ethylene-acrylic acid copolymer, and ethylene-ethyl acrylate copolymer, or a combination of any two or more thereof.
[0013] The antioxidant is any one of antioxidant 1076, antioxidant 1010, and antioxidant B125.
[0014] Technical solution three: Application of an adhesive for aramid fiber reinforced composite pipe, comprising the following steps:
[0015] 1) preparing a dopamine solution by using a buffer reagent, water and dopamine hydrochloride, and adjusting the pH value of the solution with an inorganic base to obtain a dopamine solution with a concentration of 2.5 g / L and a pH of 8.5;
[0016] 2) Impregnation reaction pretreatment, immersing the aramid fiber in a dopamine solution, and dopamine will undergo self-polymerization reaction on the surface of the aramid fiber. After the reaction is completed, the aramid fiber is taken out, washed and dried to obtain dopamine-coated aramid fiber, and the dopamine coating thickness is 40-60nm;
[0017] 3) Bonding the reinforcement layer, melting the adhesive into a colloid at a temperature of 180-200°C, applying the adhesive on the outer surface of the EVOH barrier layer of the composite pipe body, and then bonding the dopamine-coated aramid fiber in step 2) to the EVOH barrier layer, maintaining the temperature at 180-200°C and the pressure at 0.5-1.0MPa for 10-20 minutes.
[0018] 8. The use of an adhesive for aramid fiber reinforced composite pipe according to claim 7, characterized in that the aramid fiber needs to be pretreated before impregnation, the aramid fiber is first added to acetone, washed 3-5 times, then washed 3-6 times with water, taken out and placed in a 60-70°C oven for drying for 6-8 hours to obtain the pretreated aramid fiber.
[0019] The dopamine hydrochloride is chemically pure; and the buffer reagent is Tris-HCL buffer.
[0020] The inorganic base is any one of sodium hydroxide and potassium hydroxide.
[0021] In the present invention, dopamine is self-polymerized on the surface of aramid fiber to form polydopamine coated on the surface of aramid fiber, and hydroxyl and amino groups are introduced to enhance the surface roughness and polarity of the fiber, thereby enhancing the interface performance of aramid fiber. Without losing the mechanical properties of aramid fiber itself, the affinity between aramid fiber and EVOH is improved, and the introduced hydroxyl groups are used to react with the prepared adhesive to further improve the bonding between the aramid fiber reinforcement layer and the EVOH barrier layer.
[0022] The adhesive contains two materials, ethylene acrylic acid copolymer and reactive phenolic resin, which can produce bonding effects on both aramid fiber and EVOH. After construction, the polydopamine on the surface of the aramid fiber can react with the isocyanate group in the reactive phenolic resin and the carboxyl group in the ethylene acrylic acid copolymer to improve the bonding effect of the adhesive on the aramid fiber. At the same time, EVOH will also react with the isocyanate and carboxyl groups in the adhesive. The above adhesive can establish chemical bonds with the modified aramid fiber and EVOH, so that the aramid fiber reinforcement layer and the EVOH barrier layer are effectively connected into a whole, thereby improving the bonding effect.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] 1) The adhesive for aramid fiber reinforced composite pipe of the present invention has good bonding performance and is suitable for bonding aramid fiber layer and EVOH layer. The adhesive has good bonding effect on both aramid fiber and EVOH. The preparation process of the adhesive is simple, the raw materials are easily available, and it is easy to carry out large-scale industrial production;
[0025] 2) The phenolic resin in the formula also has excellent heat resistance, flame retardancy, environmental protection and renewability, making it more cost-effective;
[0026] 3) The present invention adopts aramid surface modification technology combined with adhesive technology to achieve strong bonding between the two layers. The modification method is green and environmentally friendly and does not damage the mechanical properties of the aramid fiber itself. The aramid fiber reinforcement layer and the EVOH barrier layer after bonding are firmly bonded, have high pressure bearing capacity and good heat resistance. The resulting aramid fiber reinforced composite pipe has an operating pressure of up to 4-5MPa and is suitable for a variety of pipe application fields. DETAILED DESCRIPTION
[0027] The technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments.
[0028] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the specific embodiments required to be used in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the specific embodiments described below are some implementation methods of the present invention. For ordinary technicians in this field, other specific embodiments can be obtained based on these specific embodiments without paying creative work.
[0029] The components of the embodiments of the present invention generally described and shown in the specific embodiments herein can be arranged and designed in countless different configurations. Therefore, the following detailed description of the embodiments of the present invention provided in the specific embodiments is not intended to limit the scope of the invention claimed, but merely represents selected embodiments of the present invention.
[0030] In the following examples, the melt flow rate of ethylene-vinyl alcohol copolymer is 2.0-6.0g / 10min, the melting temperature is above 190°C, and the molecular weight is 180,000-200,000. The reactive phenolic resin is an isocyanate-modified phenolic resin with a molecular weight of 1.22-1.25 million. The specific preparation method is: 5g of phenolic resin and 30ml of hexamethylene diisocyanate are mixed and then 80μl of dibutyltin dilaurate catalyst is added, and the reaction is carried out at a temperature of 30°C for 2-4h to obtain an isocyanate-modified phenolic resin. The aramid fiber is first added to chemically pure acetone, washed 3 times, then washed with water, and dried in a 60-70°C oven to obtain the pretreated aramid fiber for standby use.
[0031] Example 1
[0032] The invention discloses an adhesive for aramid fiber reinforced composite pipe, which is prepared from the following components by weight: 40 parts of ethylene-vinyl alcohol copolymer, 10 parts of reactive phenolic resin, 10 parts of compatibilizer, 0.5 parts of silicon dioxide and 0.5 parts of antioxidant. The above components are mixed in proportion and added into a twin-screw extruder for kneading. The kneading temperature is set at 190-210 DEG C and the screw speed is 300-350 rpm. The adhesive is extruded and granulated. When in use, the adhesive is melted into colloid at 200 DEG C and brushed for use.
[0033] In Example 1, the compatibilizer is ethylene-ethyl acrylate copolymer, the melt flow rate is 6.0 g / 10 min, and the ethyl acrylate content is 18.5%. The inorganic nanoparticles are silicon dioxide, and the specific surface area of silicon dioxide is 150 m 2 / g. The antioxidant is antioxidant 1076.
[0034] The method for using the adhesive for the aramid fiber reinforced composite pipe in Example 1 of the present invention comprises the following steps:
[0035] 1) preparing a dopamine solution using a buffer reagent, water and dopamine hydrochloride, first adding 1.25 g of dopamine hydrochloride to 500 ml of water, stirring and mixing, then adding 10 mM Tris-HCL buffer, and adjusting the pH value of the solution with 0.5 mol / L sodium hydroxide or potassium hydroxide to obtain a dopamine solution with a concentration of 2.5 g / L and a pH of 8.5;
[0036] 2) Pretreatment by impregnation reaction: immerse the aramid fiber in a dopamine solution and oscillate the solution at 25° C. for 24 hours. Dopamine will undergo self-polymerization on the surface of the aramid fiber. After the reaction is completed, take out the aramid fiber, wash it with deionized water, and dry it in a vacuum oven to obtain dopamine-coated aramid fiber with a dopamine coating thickness of 40-60 nm.
[0037] 3) Bonding the reinforcement layer: coating the outer surface of the EVOH barrier layer of the composite pipe body with a molten adhesive, and then bonding the dopamine-coated aramid fiber in step 2) to the EVOH barrier layer, and maintaining the temperature at 200° C. and the pressure at 1 MPa for 10 minutes.
[0038] Example 2
[0039] An adhesive for aramid fiber reinforced composite pipe is prepared from the following components by weight: 55 parts of ethylene-vinyl alcohol copolymer, 20 parts of reactive phenolic resin, 15 parts of compatibilizer, 1 part of silicon dioxide and 1 part of antioxidant. The above components are mixed in proportion and added into a twin-screw extruder for kneading. The kneading temperature is set at 190-210°C and the screw speed is 300-350 rpm. The adhesive is extruded and granulated. When used, it is melted into colloid at a temperature of 200°C and applied for use.
[0040] In Example 2, the compatibilizer is ethylene-acrylic acid copolymer, the melt flow rate is 8.0 g / 10 min, the methacrylic acid content is 20%, and the maleic anhydride content is 0.3%. The inorganic nanoparticles are silicon dioxide, and the specific surface area of silicon dioxide is 150 m 2 / g. The antioxidant is antioxidant 1076.
[0041] The method of use of Example 2 is the same as that of Example 1.
[0042] Example 3
[0043] An adhesive for aramid fiber reinforced composite pipe is prepared from the following components by weight: 60 parts of ethylene-vinyl alcohol copolymer, 25 parts of reactive phenolic resin, 20 parts of compatibilizer, 1 part of silicon dioxide and 1 part of antioxidant. The above components are mixed in proportion and added into a twin-screw extruder for kneading. The kneading temperature is set at 190-210°C and the screw speed is 300-350 rpm. The adhesive is extruded and granulated. When used, it is melted into colloid at a temperature of 200°C and applied for use.
[0044] In Example 3, the compatibilizer is ethylene-acrylic acid copolymer, the melt flow rate is 8.0 g / 10 min, the methacrylic acid content is 20%, and the maleic anhydride content is 0.3%. The inorganic nanoparticles are silicon dioxide, and the specific surface area of silicon dioxide is 150 m 2 / g. The antioxidant is antioxidant 1076.
[0045] The method of use of Example 3 is the same as that of Example 1.
[0046] Example 4
[0047] An adhesive for aramid fiber reinforced composite pipe is made of the following components in parts by weight: the adhesive resin used in this embodiment is the following components and parts by weight: 45 parts of ethylene-vinyl alcohol copolymer, 18 parts of reactive phenolic resin, 17 parts of compatibilizer, 0.8 parts of titanium dioxide, and 0.9 parts of antioxidant. The above components are mixed in proportion and added to a twin-screw extruder for mixing. The mixing temperature is set to 190-210°C, the screw speed is 300-350 rpm, and extrusion granulation is performed. When used, it is melted into a colloid at a temperature of 200°C and applied by brushing.
[0048] In Example 4, the compatibilizer is ethylene-acrylic acid copolymer, the melt flow rate is 8.0 g / 10 min, the methacrylic acid content is 20%, and the maleic anhydride content is 0.3%. The inorganic nanoparticles are zinc oxide, and the specific surface area of zinc oxide is 80 m 2 / g. The antioxidant is antioxidant 1010.
[0049] The method of use of Example 4 is the same as that of Example 1.
[0050] Example 5
[0051] An adhesive for aramid fiber reinforced composite pipe is made of the following components in parts by weight: the adhesive resin used in this embodiment is the following components and parts by weight: 50 parts of ethylene-vinyl alcohol copolymer, 15 parts of reactive phenolic resin, 20 parts of compatibilizer, 0.6 parts of zinc oxide, and 0.7 parts of antioxidant. The above components are mixed in proportion and added to a twin-screw extruder for mixing. The mixing temperature is set to 190-210°C, the screw speed is 300-350 rpm, and extrusion granulation is performed. When used, it is melted into a colloid at a temperature of 200°C and applied by brushing.
[0052] In Example 5, the compatibilizer is ethylene-vinyl acetate copolymer, the melt flow rate is 2.0 g / 10 min, and the vinyl acetate content is 33%. The inorganic nanoparticles are titanium dioxide, and the specific surface area of titanium dioxide is 50 m 2 / g. The antioxidant is antioxidant B125.
[0053] The method of use of Example 5 is the same as that of Example 1.
[0054] Comparative Example 1
[0055] A commercially available acrylic resin adhesive was used.
[0056] Comparative Example 2
[0057] A commercially available epoxy resin adhesive was used.
[0058] Table 1 below is a performance evaluation of the adhesives prepared in Examples 1-5 of the present invention and Comparative Examples 1-2.
[0059] The specific testing process is as follows:
[0060] 1) The peel strength of aramid fiber and EVOH was measured according to the GB / T2790 test method;
[0061] 2) The adhesion between a single aramid fiber and EVOH was measured by referring to the GB / T3513 test method. First, an EVOH sheet was placed in the bottom layer of the mold groove, then an adhesive and a single aramid fiber were added in the middle, and finally an EVOH sheet was placed in the upper layer. The mold was processed and formed, and the extraction strength of a single aramid fiber was tested.
[0062] 3) The interlaminar shear strength of aramid fiber and EVOH was measured according to the GB / T1450.1 test method;
[0063] 4) Based on the ASTM D7774-17 test method, the separation of aramid fiber and EVOH was observed after a fixed number of bending cycles;
[0064] 5) After the finished composite pipe is filled with water, the state is adjusted at a temperature of (23±2)℃ for at least 1h, and then the pressure is steadily increased at a rate of (1.0±0.1)MPa / min until the composite pipe ruptures or the pressure reaches 5.0MPa, and then the pressure is stopped. The pressure bearing capacity of the finished composite pipe is measured.
[0065] Table 1 Performance evaluation comparison table of various embodiments of the present invention
[0066]
[0067] After testing, it is found that the bonding effect between the aramid fiber layer and the EVOH layer of the composite tube made using the adhesive prepared in Examples 1-5 is good, and the pressure bearing capacity of the composite tube is 4-5MPa, which meets the pressure bearing standard of the composite tube; while the bonding effect between the aramid fiber layer and the EVOH layer of the composite tube made using the adhesive used in Comparative Examples 1-2 is not good, and the pressure bearing capacity of the composite tube is only 3MPa, which cannot meet the requirement that the pressure bearing standard of the composite tube is greater than 4MPa.
[0068] In summary, the bonding strength between the aramid fiber and the EVOH binder of Examples 1-5 is greatly improved, which can well solve the bonding problem between the aramid fiber and EVOH, improve the performance of the composite pipe, and meet the application fields of various pipes.
[0069] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. An adhesive for aramid fiber reinforced composite pipe, characterized in that: Made from the following components in parts by weight: 40-60 parts of ethylene-vinyl alcohol copolymer, 10-25 parts of reactive phenolic resin, Compatibilizer 10-25 parts, Inorganic nanoparticles 0.5-1 part, Antioxidant 0.5-1 part; The inorganic nanoparticles are any one of silicon dioxide, zinc oxide and titanium dioxide.
2. A method for preparing an adhesive for aramid fiber reinforced composite pipe, characterized in that: 40-60 parts of ethylene-vinyl alcohol copolymer, 10-25 parts of reactive phenolic resin, 10-25 parts of compatibilizer, 0.5-1 part of inorganic nanoparticles and 0.5-1 part of antioxidant are mixed and added into a twin-screw extruder for mixing at a mixing temperature of 190-210°C and a screw speed of 300-350 rpm, and extruded into granules to obtain a solid adhesive.
3. The adhesive for aramid fiber reinforced composite pipe according to claim 1 or 2, characterized in that: The melt flow rate of the ethylene-vinyl alcohol copolymer is 2.0-6.0 g / 10 min, the melting temperature is above 190° C., and the molecular weight is 180,000-200,000; the reactive phenolic resin is an isocyanate-modified phenolic resin with a molecular weight of 1.22-1.25 million.
4. The adhesive for aramid fiber reinforced composite pipe according to claim 1 or 2, characterized in that: The compatibilizer is any one of ethylene-vinyl acetate copolymer, ethylene-acrylic acid copolymer, and ethylene-ethyl acrylate copolymer, or a combination of any two or more thereof.
5. The adhesive for aramid fiber reinforced composite pipe according to claim 1 or 2, characterized in that: The antioxidant is any one of antioxidant 1076, antioxidant 1010, and antioxidant B125.
6. An application of an adhesive for aramid fiber reinforced composite pipe, characterized in that: The following steps are involved: 1) preparing a dopamine solution by using a buffer reagent, water and dopamine hydrochloride, and adjusting the pH value of the solution with an inorganic base to obtain a dopamine solution with a concentration of 2.5 g / L and a pH of 8.5; 2) Impregnation reaction pretreatment, immersing the aramid fiber in a dopamine solution, and dopamine will undergo self-polymerization reaction on the surface of the aramid fiber. After the reaction is completed, the aramid fiber is taken out, washed and dried to obtain dopamine-coated aramid fiber, and the dopamine coating thickness is 40-60nm; 3) Bonding the reinforcement layer, melting the adhesive into a colloid at a temperature of 180-200°C, applying the adhesive on the outer surface of the EVOH barrier layer of the composite pipe body, and then bonding the dopamine-coated aramid fiber in step 2) to the EVOH barrier layer, maintaining the temperature at 180-200°C and the pressure at 0.5-1.0MPa for 10-20 minutes.
7. The use of an adhesive for aramid fiber reinforced composite pipe according to claim 6, characterized in that: The aramid fiber needs to be pretreated before dipping. The aramid fiber is first added into acetone, washed 3-5 times, then washed 3-6 times with water, taken out and dried in an oven at 60-70° C. for 6-8 hours to obtain the pretreated aramid fiber.
8. The use of an adhesive for aramid fiber reinforced composite pipe according to claim 6, characterized in that: The dopamine hydrochloride is chemically pure; and the buffer reagent is Tris-HCL buffer.
9. The use of an adhesive for aramid fiber reinforced composite pipe according to claim 6, characterized in that: The inorganic base is any one of sodium hydroxide and potassium hydroxide.
Citation Information
Patent Citations
Low-permeation flexible fuel hose
CN101855484A
Method for producing aa polyvinyl acetate dispersion
CN104837939A
Preparation method of isocyanate modified phenolic resin foam
CN105601856A
Surface modified aramid fiber and preparation method thereof
CN105603717A
Bisphenol A isocyanate phenolic resin and preparation method thereof
CN109679039A